2015
DOI: 10.1039/c4nr05987e
|View full text |Cite
|
Sign up to set email alerts
|

Gating capacitive field-effect sensors by the charge of nanoparticle/molecule hybrids

Abstract: The semiconductor field-effect platform is a powerful tool for chemical and biological sensing with direct electrical readout. In this work, the field-effect capacitive electrolyte-insulator-semiconductor (EIS) structure - the simplest field-effect (bio-)chemical sensor - modified with citrate-capped gold nanoparticles (AuNPs) has been applied for a label-free electrostatic detection of charged molecules by their intrinsic molecular charge. The EIS sensor detects the charge changes in AuNP/molecule inorganic/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 53 publications
2
41
0
1
Order By: Relevance
“…In addition, because EGOFETs are sensitive to capacitance changes (a typical surface effect), NPs should be extremely pertinent in EGOFETs. As an example of what could be done, Poghossian et al, not in an organic-based but in a silicon-based device, reported a gating capacitive field-effect sensor [108] for detection of charged molecules using gold NPs to increase the capacitive effect ( Figure 18). Bao's group also reported biodetection using a classical bottom-gate OFET decorated with gold nanoparticles, which were used to vary spacing between receptors [109].…”
Section: Use Of Nanoparticlesmentioning
confidence: 99%
“…In addition, because EGOFETs are sensitive to capacitance changes (a typical surface effect), NPs should be extremely pertinent in EGOFETs. As an example of what could be done, Poghossian et al, not in an organic-based but in a silicon-based device, reported a gating capacitive field-effect sensor [108] for detection of charged molecules using gold NPs to increase the capacitive effect ( Figure 18). Bao's group also reported biodetection using a classical bottom-gate OFET decorated with gold nanoparticles, which were used to vary spacing between receptors [109].…”
Section: Use Of Nanoparticlesmentioning
confidence: 99%
“…Indeed, the EIS devices are electrochemical analogues of electronic elements used in conventional electronic logic gates and computing systems. Previous research, not always related to the logic gates, has demonstrated the use of EIS devices for detection of pH changes and for the analysis of enzymatic reactions and charged macromolecules (DNA, proteins, polyelectrolytes) . Thus, the use of the EIS electronic devices is straightforward for transduction of various output signals generated by the enzyme logic systems.…”
Section: Electrochemical Analysis Of the Output Signals Generated Bymentioning
confidence: 99%
“…Previous research, not always relatedt ot he logic gates, has demonstrated the use of EIS devicesf or detection of pH changes [170] and fort he analysis of enzymatic reactions [171,172] and charged macromolecules (DNA, proteins, polyelectrolytes). [173][174][175] Thus, the use of the EIS electronic devicesi ss traightforward for transduction of various output signals generated by the enzymel ogic systems.…”
Section: Transduction Of Chemical Outputs Ignals Produced By the Enzymentioning
confidence: 99%
“…Such systems can be understood as electrochemical analogues of electronic logic elements. In previous experiments, capacitive field-effect devices have been widely used for measuring the concentration of different ions and products of enzymatic reactions [23][24][25] as well as for the detection of various charged macromolecules (DNA, proteins, polyelectrolytes) and nanoobjects (e. g., gold nanoparticles, carbon nanotubes) [26][27][28][29][30][31]. Consequently, also EIS sensors can be favorably applied as a universal platform for developing various chemical and biomolecular logic gates.…”
Section: Enzyme Logic Gates Based On a Field-effect Eis Sensormentioning
confidence: 99%
“…For the OR logic-gate experiments, the multienzyme EIS sensor was exposed to buffer (pH 7.5), glucose (1 mM), ethyl butyrate (1 mM) or a mixture of glucose/ethyl butyrate solutions as biochemical inputs. The resulting EIS sensor signal, corresponding to the logic 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 output of the enzymatic reactions, was monitored by dynamic constant-capacitance measurements (ConCap [30]) using an impedance analyzer (Zahner Elektrik, Germany).…”
Section: Enzyme Logic Gates Based On a Field-effect Eis Sensormentioning
confidence: 99%